A course in language teaching - Ur, Penny (Cambridge University Press, 1999)
This important course provides a comprehensive basic introduction to teaching languages, for use in pre-service or early experience settings. It can be used by groups of teachers working with a trainer, or as a self-study resource. The Trainee's Book provides all the tasks given in the main book but without background information, bibliographies, notes or solutions. It is suitable for those studying on a trainer-led course, where feedback is readily available